Antioxidants improve the semen quality following cryopreservation in Indian yak bulls - BORAH, B K D; DEKA, B C; BISWAS, R K; CHAKRAVARTY, P; SINHA, S; AHMED, K; DEORI, S (The Indian Journal of Animal Sciences, 2021)
The present study was conducted to elucidate the effect of different antioxidants on the semen quality of cryopreserved yak semen. The ejaculates found suitable were extended (1:10) with 4 different Tris extenders by split sample technique containing different antioxidants in each of 3 extenders, viz. Taurine @ 50 mM, Trehalose @ 100 mM or vitamin E @ 2 mM and one control (without additive). The sperm motility, live sperm, HOSTreacted sperm, total incidence of acrosomal changes and extracellular release of ALT and AST differed significantly between antioxidants. Total sperm motility, live sperm and HOST-reacted sperm were significantly higher and total incidence of acrosomal changes and extracellular release of AST were significantly lower in extender containing antioxidants than that in control. The difference between taurine, trehalose and vitamin E was not significant for parameters like sperm motility, HOST-reacted sperm and extracellular release of ALT. The per cent live sperm was significantly higher and total incidence of acrosomal changes was significantly lower for taurine than for trehalose and vitamin E. The extracellular release of ALT was significantly lower in extender containing taurine or trehalose than in control while the extracellular release of AST was significantly lower in the extender containing taurine than that in containing trehalose, vitamin E and control. The findings of the present study revealed that addition of taurine, trehalose and vitamin E in Tris extender significantly improved the post thaw quality of yak semen. Among the antioxidants evaluated, 50 mM of taurine in Tris extender could be effectively used to obtain better quality of frozen thawed yak semen.